Influence of vegetation to removal organic load and nutrients in a septic waste treatment system - Silva Júnior, Édio Damásio da; Almeida, Rogério de Araújo; Siqueira, Elisa Rodrigues; Silva, Ábio Roduvalho da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The use of constructed wetlands for septic waste treatment has been little explored in developing countries, mainly due to the limited information available about the technology. The real influence of vegetation on waste treatment is one of the points in question. This paper aims to evaluate the influence of vegetation vetiver grass (Chrysopogon zizanioides) on the removal of pollutants and the stability of a mineral beds system for septic waste treatment. Two beds were built (with and without vegetation) for the disposal and treatment of septic waste in tidal flow. Raw waste and treated effluent were analysed in both cells. The percentage efficiency of removal of pollutants from each bed was evaluated. In addition, dispersion and correlation analysis of applied pollutant loads and effluent concentrations were carried out at each bed. Planted cell showed better results in percentage efficiency of removal of pollutants. Effluent concentrations were lower in planted cell for the applied loads of biochemical oxygen demand (BOD) and total phosphorus (TP). For ammonia, the cell without plants had lower effluent concentrations. In general, in both cells were observed low-medium associations between applied loads and effluent concentration. The bed with plants was shown to be more stable and with greater capacity of amortization of the pollution for the parameters BOD and TP.